Tinjauan Yuridis Praktek Pengalihan Piutang (Cessie) Di Bank Bukopin Cabang Mataram - Maharani Alika Novita Sari; Aris Munandar (Fakultas Hukum Universitas Mataram, 2022)
This research has the purpose to find out the cessie implementation at Bukopin Bank Mataram Branch, the legal consequences and find out wether the cessie implementation at Bukopin Bank Mataram branch is according with Article 613 Indonesia Civil Code. This research uses normative-empirical legal research method namely the research method combined the normative elements ( legislation or juridical) and adding with fiel data or empirical elements. Cessie is a transferring accounts receivable and another intangible thing by an authentic deed or non-authentic deed. This is make the transfered of property right occurred to other legal subject. In this research, the cessie implementation is according with Article 613 Indonesia Civil Code, because with authentic deed and the mortgage have been registered. The legal consequence for the cange of creditor position is the mortgage and the other billing rights moving also to the new creditor.